Adhesion maturation of neutrophils on nanoscopically presented platelet Glycoprotein Ibα - Kruss, Sebastian; Erpenbeck, Luise; Amschler, Katharina; Mundinger, Tabea A.; Boehm, Heike; Helms, Hans-Joachim; Friede, Tim; Andrews, Robert K.; Schön, Michael P.; Spatz, Joachim P. (ACS nano, 2013)
Neutrophilic granulocytes play a fundamental role in cardiovascular disease. They interact with platelet aggregates via the integrin Mac-1 and the platelet receptor glycoprotein Ibα (GPIbα). In vivo, GPIbα presentation is highly variable under different physiological and pathophysiological conditions. Here, we quantitatively determined the conditions for neutrophil adhesion in a biomimetic in vitro system, which allowed precise adjustment of the spacings between human GPIbα presented on the nanoscale from 60 to 200 nm. Unlike most conventional nanopatterning approaches, this method provided control over the local receptor density (spacing) rather than just the global receptor density. Under physiological flow conditions, neutrophils required a minimum spacing of GPIbα molecules to successfully adhere. In contrast, under low-flow conditions, neutrophils adhered on all tested spacings with subtle but nonlinear differences in cell response, including spreading area, spreading kinetics, adhesion maturation, and mobility. Surprisingly, Mac-1-dependent neutrophil adhesion was very robust to GPIbα density variations up to 1 order of magnitude. This complex response map indicates that neutrophil adhesion under flow and adhesion maturation are differentially regulated by GPIbα density. Our study reveals how Mac-1/GPIbα interactions govern cell adhesion and how neutrophils process the number of available surface receptors on the nanoscale. In the future, such in vitro studies can be useful to determine optimum therapeutic ranges for targeting this interaction.
Gesehen am 17.06.2021